PRAKTIKALITAS MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN APLIKASI POWTOON - Yolanda, Nela Sari; Laia, Niscaya (STKIP Pesisir Selatan, 2022)
This study aims to determine the practicality of mathematics learning media created using the powtoon application for Class XI Busana students at SMK Negeri 6 Padang. This research will reveal the level of practicality of using learning media using the powtoon application both from teachers and students after using this learning media in the learning process. The learning media that has been developed and the previous questionnaire sheets have been validated by the validators.Based on the results of the research, it shows that the learning media developed are practically visible from the practicality test results obtained from the teacher's response and student responses. The practicality test results obtained were 81,73% for teacher responses and 77,03% for student responses.